2022
DOI: 10.1021/acs.est.2c01119
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Transformation Pathways of a Short-Chain Chlorinated Paraffin Congener, 1,2,5,6,9,10-C10H16Cl6, in a Rice Seedling Hydroponic Exposure System

Abstract: In this work, a typical congener of short-chain chlorinated paraffins (SCCPs) with six chlorine atoms (CP-4, 1,2,5,6,9,10-C10H16Cl6, 250 ng/mL) was selected to elaborate the comprehensive environmental transformation of SCCPs in rice seedling exposure system. CP-4 was quickly absorbed, translocated, and phytovolatilized by seedlings with a small quality of CP-4 (5.81–36.5 ng) being detected in the gas phase. Only 21.4 ± 1.6% of an initial amount (10,000 ng) of CP-4 remained in the exposure system at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…This section discusses CPs in marine organisms, revealing their widespread occurrence, bioaccumulation, and biomagnification in the food webs of various marine environments, and potential risk to human health (Figure , Figure , and Table S5). Generally, markedly higher detection frequency occurred in SCCPs and MCCPs than in vSCCPs and LCCPs in marine organisms, which could be owing to a combination of the current production, use, emission of CPs, and their partitioning and transformation behaviors worldwide. , …”
Section: Distribution Of Cps In the Marine Environmentmentioning
confidence: 98%
“…This section discusses CPs in marine organisms, revealing their widespread occurrence, bioaccumulation, and biomagnification in the food webs of various marine environments, and potential risk to human health (Figure , Figure , and Table S5). Generally, markedly higher detection frequency occurred in SCCPs and MCCPs than in vSCCPs and LCCPs in marine organisms, which could be owing to a combination of the current production, use, emission of CPs, and their partitioning and transformation behaviors worldwide. , …”
Section: Distribution Of Cps In the Marine Environmentmentioning
confidence: 98%
“…The metabolism of CPs has been indicated in previous studies by following radioactively labeled CPs or untargeted screening by high-resolution MS techniques. The natural isotopic pattern of chlorine atoms is a characteristic distinguishing the chlorine-containing metabolites from the endogenous metabolites, which provides excellent evidence to elucidate the formula of the potential CP metabolites . Nevertheless, the in vivo study of CP metabolism has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, root exudates and/or rhizosphere microorganisms might also facilitate the transformation of phenamacril in hydroponic solution. 38 During 7− 28 days of exposure, M-232-2 was the major metabolite in the hydroponic solution, which accounted for 64%−86% of the total peak areas of all metabolites. More kinds of hydrolyzed metabolites (M-232-1/2/3/4) were extensively formed in plant tissues, and they contributed 37%−84% of the total measured peak areas in both plant tissues.…”
Section: ■ Results and Discussionmentioning
confidence: 99%